Clinical and demographic predictors of the need for pharmacotherapy in neonatal abstinence syndrome - Bibi, Shawana; Singh, Rachana; Breeze, Janis L.; Nelson, Jason; Kraft, Walter K.; Davis, Jonathan M. (Frontiers in Pediatrics, 2025)
ObjectiveDevelopment and validation of a clinical prediction model for receipt of pharmacotherapy for Neonatal Abstinence Syndrome (NAS).Study designData from three cohorts included in- utero opioid exposed neonates ≥37 weeks gestation. Primary outcome was the receipt of pharmacotherapy utilizing a modified Finnegan Neonatal Abstinence Scoring System (FNASS). A stepwise multivariable logistic regression model was built and internally validated.ResultsOf 698 infants included, 430 received pharmacotherapy. The final model included seven predictors of receipt of pharmacotherapy: gestational age, exposure to maternal breast milk, type of maternal opioid medication, and exposure to heroin, cocaine, benzodiazepines, and/or antipsychotic medications. The model had an AUROC of 0.68 (95% CI: 0.64–0.72; optimism corrected 0.65).ConclusionOur prediction model was parsimonious and identified seven predictors associated with the need for PT. Larger cohort studies are needed to more definitively establish risk of significant NAS requiring pharmacotherapy.